2022
DOI: 10.1063/5.0090009
|View full text |Cite
|
Sign up to set email alerts
|

Noncollinear magnetic order in epitaxial thin films of the centrosymmetric MnPtGa hard magnet

Abstract: Magnetic systems exhibiting spin-canted states have garnered much attention recently for their promising rich exotic properties driven by the real-space spin textures and competing magnetic orders. In this study, we present the structural and magnetic properties of hexagonal 60 nm MnPtGa epitaxial thin films grown by magnetron sputtering on Al2O3(0001) single-crystalline substrates. The MnPtGa film crystallizes in the centrosymmetric P63/ mmc (No. 194) space group, showing perpendicular magnetic anisotropy alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Figure 1a shows the primitive unit cell of hexagonal MnPtGa crystal, together with the noncollinear magnetic structure formed by Mn spins. [ 6 ] Resorting to single‐crystal neutron diffraction, on a nominally identical 60 nm thick (0001)‐Al 2 O 3 /MnPtGa film, we found that in zero external magnetic fields, the magnetic ground state of the system is composed of ferromagnetically aligned Mn‐spins in the basal plane, with an in‐plane (IP) moment component ordering antiferromagnetically along the [0001] out‐of‐plane direction. Together with the magnetocrystalline anisotropy, these competing exchange interactions set a global staggered spin‐canted state, where the Mn‐spins are found to tilt 20 o away from the c ‐axis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1a shows the primitive unit cell of hexagonal MnPtGa crystal, together with the noncollinear magnetic structure formed by Mn spins. [ 6 ] Resorting to single‐crystal neutron diffraction, on a nominally identical 60 nm thick (0001)‐Al 2 O 3 /MnPtGa film, we found that in zero external magnetic fields, the magnetic ground state of the system is composed of ferromagnetically aligned Mn‐spins in the basal plane, with an in‐plane (IP) moment component ordering antiferromagnetically along the [0001] out‐of‐plane direction. Together with the magnetocrystalline anisotropy, these competing exchange interactions set a global staggered spin‐canted state, where the Mn‐spins are found to tilt 20 o away from the c ‐axis.…”
Section: Resultsmentioning
confidence: 99%
“…Together with the magnetocrystalline anisotropy, these competing exchange interactions set a global staggered spin‐canted state, where the Mn‐spins are found to tilt 20 o away from the c ‐axis. [ 6 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations